MEDIATION AS A METHOD OF CONFLICT RESOLUTION: CHARACTERISTICS AND DIFFERENCES FROM NEGOTIATIONS AND ARBITRATION - LEVCHENKO, Diana; KALININA, Natalia; OKUNIEV, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The paper reveals the features of mediation as a method of conflict resolution, which include: voluntary participation and interaction of mediation participants; special status of the mediator (combination of formal, ethical and procedural requirements); confidentiality of the mediation process; flexibility and adaptability of the mediation procedure; consensus approach to conflict resolution; recognition of the significance of the emotional and psychological aspect of the conflict; minimization of financial and time costs; active participation of the parties to the conflict in the decision-making process; responsibility of the parties to the conflict for the implementation of the agreements reached; restoration of conflict relations between the parties. The differences between negotiations and mediation are identified, in particular: 1) in mediation there must be a third party - a mediator, unlike negotiations in which the parties can involve a negotiator, and can conduct negotiations independently; 2) a clear structure of the mediation process, unlike negotiations that are not formalized; 3) the choice of negotiations or mediation depends on the level of conflict between the parties (negotiations are used at a lower level of conflict, when the parties are ready to interact, and mediation is mainly used in cases of a high level of conflict between the parties, when a communication barrier arises between the parties); 4) different emphasis on the use of conflict resolution tools (in negotiations - discussions or arguments, as tools for obtaining a favorable result; in mediation - dialogue, as a tool for forming a mutually beneficial result); 5) the binding nature of the agreement based on the results of mediation, in contrast to negotiations (except for cases of concluding binding contracts). The emphasis is placed on the differences between mediation and arbitration, in particular: 1) voluntary mediation process or quasi-judicial proceedings; 2) different roles of the third party - the mediator is a facilitator, the arbitrator plays the role of a judge; 3) the method of obtaining the result of the dispute resolution - in mediation, the parties independently determine the outcome of the mediation, in arbitration, the decision is made by the arbitrator and is binding; 4) the degree of procedural regulation - in mediation, there is no clear regulation, and the process is flexible, and the arbitration procedure is regulated by national and international legislation; 5) the time of the process (the mediation process, in most cases, takes place in a shorter time than the arbitration process); 6) the consequences of the process for relations - in mediation, the emphasis is on improving and maintaining further relations between the parties, the arbitration process is adversarial, without the goal of preserving relations.
Keywords: alternative dispute resolution; arbitration; ethics; conflict; mediator; negotiations; litigation